Building National Resilience Through Digital Literacy for Gen Z - Ahmad Yazid Affandi; Andara Adista Khairunisa (Konsultan Jurnal Ilmiah Indonesia, 2026)
This study examines the role of digital literacy in strengthening national resilience amid the growing circulation of hoaxes among Generation Z in Indonesia. The vulnerability of Gen Z to misinformation is primarily linked to their limited ability to verify and evaluate digital content, which poses risks to social cohesion and national stability. Using a descriptive qualitative approach through literature review, this research analyzes academic publications from 2019-2025 concerning digital literacy, misinformation, and information security. The synthesis of the literature indicates that higher levels of digital literacy, particularly skills in accessing, evaluating, and producing information, significantly reduce the spread of hoaxes and enhance public resilience against information disorders. This study highlights the importance of strengthening digital literacy education and implementing public policies that support responsible digital engagement. Digital literacy is therefore positioned as a crucial foundation for national resilience, especially in maintaining stability and unity in an increasingly digital society.